Dental Carries Prevalence and Associated Factors of Secondary Level Students in Eastern Nepal - Bhujel, Kajol; Poudyal, Jiwan Kumar; Parajuli, Sumitra; Gaire, Pratikshya; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2024)
Background: Dental caries or a tooth decay is a common oral health condition characterized by demineralization of tooth enamel and subsequent formation of cavities It is a global public health problem and influence the overall health of children. Method: A cross-sectional study was conducted among 343 secondary level school students by complete enumeration sampling method. A pretested, standardized, closed-ended questionnaire and a standard Decayed, Missing, and Filled primary Teeth (DMFT) tools were adopted to find out the prevalence and associated factors of Dental Caries. Face to face interview and oral assessment under natural day light were uses for data collection methods. Data were coded, entered, cleaned and analyzed by using SPSS version 22. Descriptive and bi-variate statistics were employed to test the association between dependent and independent variables. P-value less than 0.05 was taken as significant association and result was presented in text, tables and graph. Result: The overall prevalence of dental caries was 68.5% with a mean and SD of DMFT of 1.53±1.462 and female students were most sufferer (70.1%) from dental caries. There was a significant association of dental caries with mother’s educational status (p=0.009), consumption of sugary tea/coffee (p=<0.001), frequency of soft drinks consumption (p=0.004), frequency of tooth brushing (p=<0.001) and changing time of new tooth brush (p=<0.001). Conclusion: The study found a high prevalence of dental caries among the students, which were attributed to consumption of sugary foods and drinks and poor oral hygiene practices. The researchers hold a strong conviction that relevant authorities can provide the necessary actions to raise the awareness regarding the issue.